Funktion, Gestaltung und Einsatz des Lehrbuchs im Fremdsprachenunterricht für Fortgeschrittene - Hellmich, Harald (Wydawcnictwo Naukowe UAM, 1988)
A textbook has both instructive and educative functions — op the one hand it informs about linguistic norm and stimulates speech behaviour, on the other hand it expresses, in the form of texts, the given non-linguistic reality, the target language milieu, and social and individual consciousness, which foreign language learners have to relate to. From the didactic point of view there are t hree types of texts: basic texts introducing topics, pattern texts for speech production and end-product texts, the results of learners’ spoken and written performances. A detailed discussion of different kinds of texts on the ground of their communicative aspect follows. Referring to the threefold didactic functions of a text three sets of tasks and exercises are mentioned: the set designed to introduce texts, the set interpreting texts and the set exploiting texts.